Report of the Working Group on Rainfed Areas for Formulation of XI Five Year Plan - Planning Commission (Planning Commission, 1999)
Statistical Review of Rainfed Agriculture Out of an area of 329 m.ha the gross sown area during last 15 years remained almost stagnant at 184.5 m.ha the net sown area is gradually decreasing from year 1999. During the corresponding period, increase in area sown more than once (10.69%), area under non-agricultural uses (9.85%), fallow land (12.73%), current fallows (16.51) was observed.
Planning Commission Government of India
Planning Commission Government of India